Analysis of Energy Dissipation and Ductility of castellated Steel Links in Eccentrically braced Frame under Lateral Cyclic Loading - Sandy, Desi; Parung, Herman; Irmawaty, Rita (Engineering, Technology & Applied Science Research, 2025)
High-ductility and high-strength steel is highly suitable for earthquake-affected areas. An Eccentric Braced Frame (EBF) with replaceable links is a system that provides extraordinary ductility and resistance to earthquake-induced forces. The Eccentrically Braced Frame (EBF) design aims to combine the advantages of the lateral load-resisting systems of the Moment-Resisting Frame (MRF) and the Concentrically Braced Frame (CBF) into a single structural system to resulting in a structure with high elastic stiffness and high energy dissipation during a severe earthquake. In this case, steel castellated beams are used as beam spans. Castellated beams can increase the moment of inertia (I) and reduce the weight of the element. The use of castellated beams has advantages, such as geometric efficiency, especially at long spans. The objective of this research is to analyze the behavior of EBF in steel castellated connections using an experimental method. This study analyzes two specimens, CL450 and CL870, with link lengths of 450 mm and 870 mm, respectively. The results showed that the CL870 specimen had higher strength compared to the CL450 specimen. CL870 dissipated more energy than CL450, indicating that longer links result in greater energy dissipation. Additionally, both specimens exceeded the required ductility values, with an average ductility greater than 4, demonstrating that they have good flexibility and deformation capacity. Overall, CL870 excels in terms of strength, energy dissipation, and ductility.